Linking self-efficacy and decision-making processes in developing soccer players. (November 2018) - Musculus, Lisa; Raab, Markus; Belling, Patrick; Lobinger, Babett
Abstract: Objectives: In sports, adults with high self-efficacy have been shown to select their first option as the final choice more often in a dynamic decision-making test. Addressing the link between self-efficacy and decision making early in age could benefit the developmental potential of athletes. In this study, we examined the link between developing players' decision self-efficacy and their decision-making processes comprising option generation and selection. Further, we explored the effect of time pressure on developing athletes' decision making. Design: Developing athletes ( N  = 97) of two different age groups were asked to report their self-efficacy and to perform a dynamic decision-making task, in which time pressure was experimentally manipulated. Method: 48 younger ( M age  = 8.76, SD  = 1.15) and 49 older ( M age  = 12.18, SD  = 0.87) soccer players participated. Participants were randomly presented with video scenes of soccer match play. At the point of temporal occlusion, participants generated options about the next move. After generation, participants selected among the generated options their best option and indicated their decision and motor confidence. Results: The self-efficacy of developing players was neither related negatively to dynamic inconsistency nor positively to option or decision quality, but self-efficacy was positively related to motor confidence in the best option. Further, time pressure improved option and decision quality. Conclusion: Decision-making processes have been scrutinized by showing that developing players' self-efficacy links to their motor skills rather than to their cognitive evaluation and by specifying the adaptation to time pressure. Thereby, results extend current theorizing on decision making. Highlights: Self-efficacy of developing players was related to their motor confidence. Self-efficacy was not negatively related to dynamic inconsistency. Among the developing players, older players generated better first options. Time pressure fostered option and decision quality.